The movement patterns of elephant in the Kruger National Park in response to culling and environmental stimuli - Whyte, Ian (Pachyderm, 1993)
The elephant population of the area now comprising the Kruger National Park (KNP) was almost exterminated before the proclamation of the area as a game reserve in 1903. The population then increased gradually through immigration from Zimbabwe and through natural increases until 1967 when the decision was made to control the population through culling. The methods used and results are discussed and conclusions to the findings given.